Adhesion Detection Analysis by Modeling Rail Wheel Set Dynamics under the Assumption of Constant Creep Coefficient - Soomro, Zulfiqar Ali (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2014)
Adhesion level control is very necessary to avoid slippage of rail wheelset and track from derailment for smoothing running of rail vehicle. In this paper the proper dynamics of wheelset for velocities acting in three dimensions of wheelset and rail track has been discussed along with creep forces on each wheel in longitudinal, lateral and spin directions has been enumerated and computed for suitable modeling. The concerned results have been simulated by Matlab code to observe the correlation of this phenomenon to compare creepage and creep forces for detecting adhesion level. This adhesion identification is recognized by applying coulomb’s law for sliding friction by comparing tangential and normal forces through co-efficient of friction